Finite element analysis (using ANSYS) of curvature-correction of in-grown human toe-nail with corrective elastic strips pasted on to the nail surface - Koh, Kai Xin (Nanyang Technological University, 2024)
Ingrown toenail is a common foot problem particularly among the elderly. One of the ways to correct the ingrown toenail is to paste an elastic strip on the curved ingrown toenail so that the strip applies restoring (corrective) forces on the nail. These corrective forces tend to reduce the curvature of the ingrown toenail. This Final Year Project (FYP) focuses on the mechanical effectiveness of corrective elastic strips for the treatment of ingrown toenails. The effectiveness is studied using Finite Element Analysis (FEA) carried out in ANSYS Mechanical APDL. A 2D finite element model is used to analyse the distribution of von-Mises stress in the elastic strip and contact pressure on the toenail.